Virtual money – money of the future? Economic aspects, financial and legal environment - Smus, Tomasz R. (Pieniądz wirtualny kolejną formą pieniądza? Aspekty ekonomiczne, finansowe i prawne, 2012)
The paper explores virtual reality and objects as well as the dawn of the virtual money age on the Internet and the related issues of its economic, financial and legal environment. The author will focus on presenting the phenomenon of omnipresent virtual reality including the birth of virtual money, and next attempts to define the form of money used nowadays, to conclude with the identification of virtual money characteristics as a new form of payment in electronic environment compared to electronic money against the background of regulations of Polish law
Nauki o Finansach = Financial Sciences, 2012, Nr 1 (10), s. 116-127
Keywords: virtual money; electronic money; e-payments; pieniądz wirtualny; pieniądz elektroniczny; e-płatności